何必写信：罗马帝国总督的沟通问题[Why Write Letters: Communication Issues of Roman Imperial Governors] - Ching-Yuan Wu (北京大学“历史与文学文本中的古代帝国”人文论坛[Humanities Forum on "Ancient Empires in Historical and Literary Texts", 2023)
The newly discovered gubernatorial edict from Laodicea, in which the proconsul of Asia (likely Marcus Ostorius? Scapula) issued a series of orders, contains references to precedents from his predecessors, including edicts from the proconsul Cornelius Tacitus and his deputy Saenius Sabinus, and a letter from the proconsul Vicirius Martialis. Why did Martialis issue a letter instead of an edict? What was the function of Martialis' correspondence, and what did it achieve? In Oliver, Greek Constitutions, pp. 20-21, Augustus and later principates continued to use written proclamations in edict form as a way of communicating with provincials, a tradition practiced by Roman magistrates in the Republic. We also learn that edicts were essentially "open letters to whom it might concern," and were not unlike epistles in terms of preparation, at times not carefully distinguished by the secretaries that prepared them. If there were edict and epistolary forms, it is not immediately clear how they differed in function and perception, both from the perspective of the senders and their intended recipients. Gubernatorial communications have received treatment by Meyer-Zweiffelhoffer (2002), Kokkinia (2003, 2004) Lavan (2013). Kokkinia states that there are approximately 90 examples, and they point to the pattern in which most governors were acting upon local requests to interevene (Kokkinia 2004: 49). If the purpose was to intervene, at what point will an epistle be no longer enough, but an edict will? This paper will first use Paulus Fabius Maximus' letter-edict to discuss a classical case in which an attempt to write a letter took a sinister turn towards an edict. We will then examine a range of cases including those from the Opramoas dossier to consider the various epistolary approaches that the Roman governors took in responding to local situations. The paper will use this assembled corpus to interpret the Vicirius Martialis' letter from both its immediate communicative context and also the general tradition in official correspondence. This paper also touches on the broader question of why governors need to write letters, when they could have just issued edicts, and what letters can do that edicts could not.